Use of Selected Telemedicine Tools in Monitoring Quality of In-Hospital Cardiopulmonary Resuscitation: A Prospective Observational Pilot Simulation Study - Więch, Paweł (Med Sci Monit, 2019)
BACKGROUND: The aim of this study was to assess the quality of in-hospital cardiopulmonary resuscitation components performed by nurses under simulated conditions, with the use of selected telemedicine tools. MATERIAL/METHODS: This prospective observational pilot simulation study was carried out with a group of 48 nurses working in hospital wards specializing in conservative treatment (HOS/C=22; mean age of 30.27 years; SD 9.30) or interventional therapy (HOS/I=26 nurses; mean age of 30.35 years; SD 9.77). Each nurse performed CPR for two minutes (a sequence of 30 compressions: 2 breaths) on a Laerdal Resusci-Anne manikin that was positioned on an examination couch using a self-inflating bag and face mask in accordance with their knowledge of and skills related to in-hospital resuscitation. The study was conducted in two stages, separated with an intervention (refresh online training by using Polycom RealPresence Group Devices). Analyses of selected chest compression and relaxation parameters were performed with the use of the TrueCPR Coaching Device. RESULTS: The finding showed improved compression depth (HOS/C: 46.68 mm vs. 51.50 mm; HOS/I: 46.92 mm vs. 50.57 mm), improved full recoil (HOS/C: 81.68% vs. 94.67%; HOS/I: 75.92% vs. 82.13%), and sustained standard compression rate (HOS/C: 115.23/min vs. 105.11/min; HOS/I: 113.65/min vs. 111.04/min) in the study group, 2 months after the intervention. A significant difference between the groups was observed in the rate of chest compressions with complete recoil (HOS/C: 94.67% vs. HOS/I: 82.13%; p<0.042). CONCLUSIONS: The use of selected telemedicine tools leads to improved chest compression and relaxation parameters during in-hospital sudden cardiac arrest.